Effect of anode morphology on the performance of thin film solid oxide fuel cell with PEALD YSZ electrolyte. (15th June 2016) - Park, Taehyun; Cho, Gu Young; Lee, Yoon Ho; Tanveer, Waqas Hassan; Yu, Wonjong; Lee, Yeageun; Kim, Yusung; An, Jihwan; Cha, Suk Won
Abstract: Thin film solid oxide fuel cells (SOFCs) with Pt anode, yttria-stabilized zirconia (YSZ) electrolyte, and Pt cathode were fabricated based on nano-porous substrate. Pt and YSZ were deposited using sputter and plasma-enhanced atomic layer deposition (PEALD), respectively. Here, two types of Pt anode, i.e., dense and porous, were prepared to compare the performances of the fuel cells. The performance of the fuel cell with the porous Pt anode showed higher peak power density (194 mW/cm 2 ) than that with the dense Pt anode (178 mW/cm 2 ) at 500 °C. Through the analyses via scanning electron microscopy and electrochemical impedance spectroscopy (EIS), it was found that the increase of the performance was attributed to the enhanced supply of the hydrogen into the porous anode and resulting enhancement of charge transfer and mass transport. In the EIS results, the anodic charge transfer resistance of the fuel cell with the dense Pt anode was higher than that of the porous Pt anode, even though the porous Pt anode is thicker than the dense Pt anode. The result from a high-resolution transmission electron microscopy and electron-dispersive spectroscopy images showed that anodic pores were slightly filled with YSZ due to the low conformality of PEALD, resulting in the additional formation of triple phase boundaries. Graphical abstract: